Mediasi Oleh Kepala Desa dalam Penyelesaian Sengketa Tanah Melalui Non Litigasi (Studi di Dea Lanta Kabupaten Bima) - Bima Indrayana; Taufik Firmanto; Kasmar Kasmar (Jurnal Hukum Lex Generalis, 2025)
This study examines the role of village heads in mediating land dispute resolution through non-litigation channels in Lanta Village, Bima Regency. The background of this study is based on the high number of land dispute cases that are not resolved through the courts. The results of the study indicate that village heads have a central role as mediators trusted by the community, with a family and deliberation approach. In conclusion, mediation by village heads can be an alternative for effective, efficient, and equitable dispute resolution, although it still faces obstacles such as limited authority and potential conflicts of interest.